TRAINING FOR HEALTH CADRES IN CONTROLLING RISK FACTORS FOR NON-COMMUNICABLE DISEASES AS AN EFFORT TO REALIZE A HEALTHY PRODUCTIVE AGE - Ratna Yunita Sari; Riska Rohmawati; Imamatul Faizah; Siti Nur Hasina; Rahmadaniar Aditya Putri (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
The significant increase in the incidence of Non-Communicable Diseases and progressive diseases makes the burden increase for the community and the government, as a result, the handling of the disease takes a long time, and the cost of treatment is large, causing individuals to become unproductive or less productive and the highest cause of death. Non-communicable diseases can be prevented by controlling risk factors. This service activity has the aim of increasing the knowledge and skills of health cadres in controlling non-communicable disease risk factors in an effort to realize a healthy productive age. Community service activities are carried out in the area of RW 05, Wonokromo Village, Surabaya City. The method of carrying out activities uses a participatory approach by way of lectures, discussions, brainstorming, and direct demonstrations to increase the knowledge of cadres in non-pharmacological therapy in the prevention of PTM. This activity was held in June-July 2022 and was attended by 15 cadres. The results of the evaluation of the training activities obtained an increase in knowledge and skills as indicated by the pretest results of 60% increasing to 80% posttest results and an increase in good cracks where cadres can check blood pressure, temperature measurement, height measurement, weight measurement, abdominal circumference, check blood sugar, uric acid, and check cholesterol independently and in accordance with standard operating procedures and most of the cadres are able to provide counseling to residents, so that it is hoped that this will reduce the incidence of non-communicable diseases and maintain the health status of residents in their target areas.